2014
DOI: 10.1186/1476-511x-13-190
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of EPA and DHA in fish oil nutritional capsules by GC-MS

Abstract: BackgroundFish oil is a popular nutritional product consumed in Hong Kong. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are the two main bioactive components responsible for the health benefits of fish oil. Market survey in Hong Kong demonstrated that various fish oil capsules with different origins and prices are sold simultaneously. However, these capsules are labelled with same ingredient levels, namely EPA 180 mg/g and DHA 120 mg/g. This situation makes the consumers very confused. To evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…Several publications have studied the correctness of the manufacturers' information in fish oil supplements (Opperman et al, ; Osadnik and Jaworska, ; Yi et al, ). For example, Osadnik et al found that, for the majority of their tested products in the Polish market, there was consistency in the total amount of DHA and EPA claimed on the label, while Opperman's group reported that the n‐3 supplements available in the South African market contained ≤89% of the stated content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several publications have studied the correctness of the manufacturers' information in fish oil supplements (Opperman et al, ; Osadnik and Jaworska, ; Yi et al, ). For example, Osadnik et al found that, for the majority of their tested products in the Polish market, there was consistency in the total amount of DHA and EPA claimed on the label, while Opperman's group reported that the n‐3 supplements available in the South African market contained ≤89% of the stated content.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in their extraction and derivatization of the FA, they follow multistep procedures and/or involve long heating times (among others, Opperman et al, ), high temperatures (Rincón‐Cervera et al, ), costly automated instrumentation (Roberts, et al, ; Stuff and Whitecavage, ), high‐resolution equipment (Osadnik and Jaworska, ), or special analysis software (Kanable et al, ). Many of them have been conducted in other countries and only concentrate in supplements obtained in local markets (Opperman et al, ; Osadnik and Jaworska, ; Yi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed could provide a viable alternative source where, for example, in Palmaria palmata, despite having a lipid content of just 2.3% at the time of sampling, 50% (11.6 mg/g biomass) of this lipid was in the form of EPA (20:5). Given that the EPA content of commercially available fish oil supplements range between~40-500 mg/g [20], it is clear that seaweeds could make a big impact as a substitute feed stock for the production of high-value omega-3 animal feed supplements, nutraceuticals, pharmaceuticals and cosmetics. Indeed, the recommended dietary ratio of ω-6: ω-3 PUFA is less than 10 [16] and with all of the seaweeds analysed here having a ratio of between 0.15 and 2, so offering a significant advantage to the food and feed industries.…”
Section: Lipid and High-value Omega-3 Oil Contentmentioning
confidence: 99%
“…Furthermore, multiple publications have raised concerns regarding the variability of omega‐3 content in dietary supplements as well as the quality and purity of these products (Kleiner, Cladis, & Santerre, ; Mason & Sherratt, ; Shim, Santerre, Burgess, & Deardorff, ; Truong, Johnson, & Gabriel, ; Tur, Bibiloni, Sureda, & Pons, ; Weitz, Weintraub, Fisher, & Schwartzbard, ; Zargar & Ito, ). For example, studies have shown that the actual concentrations of DHA and/or EPA in omega‐3 supplements may be far below or far in excess of the labeled amounts (Albert et al., ; Kleiner et al., ; Shim et al., ; Yi et al., ). In addition, omega‐3 dietary supplements are not “pure” and may contain contaminants and/or harmful/unwanted ingredients such as high concentrations of cholesterol, saturated fats, lipid peroxides, and oxidation products (Albert et al., ; Jackowski et al., ; Mason & Sherratt, ; Ritter, Budge, & Jovica, ; Truong et al., ; Tur et al., ; Weitz et al., ; Zargar & Ito, ).…”
Section: Overview Of Omega‐3 Dietary Supplementsmentioning
confidence: 99%